A comparative study of the quality differences and seasonal dynamics of flavonoids between the aerial parts and roots of Scutellaria barbata - Cheng, Yijie; Cao, Wenxin; Guo, Ru; Chen, Ruihuan; Li, Xiaofan; Qian, Da; Xu, Jingyuan (Frontiers in plant science, 2024)
D. Don is a widely cultivated Chinese herbal medicine known for its medicinal properties. However, differences in the spatial distribution of metabolites, accumulation patterns of flavonoids, and pharmacological activities between the aerial parts and roots of still remain unclear, posing challenges for its standardized cultivation and quality control. This study aimed to elucidate the quality differences between these plant parts and clarify their seasonal variations. The chemical profiles were qualitatively analyzed by UPLC-QTOF-MS/MS. The accumulation patterns of total flavonoids, scutellarin and baicalin in different parts of were quantitatively analyzed by UV and HPLC respectively. The differences of pharmacological efficacy were evaluated by antioxidant assays and CCK-8 assay. In this research, there were 46 compounds identified in that included 44 flavonoids. The aerial parts primarily accumulate flavonoids with 4'-hydroxyl group, while the root mainly accumulate flavonoids without this group. Additionally, the accumulation and variation of flavonoid components were seasonally dependent, with the aerial parts reaching peak content in spring during vigorous vegetative growth and the roots accumulating most flavonoids in autumn. The extracts from both parts exhibited antioxidant activity and inhibitory effects on cancer cell proliferation, with notable differences between them. This study provides valuable insights into the quality differences and seasonal dynamics of the different parts of , offering a reference for standardized harvesting and quality control.